Phenomenology and Sociological Research: The Constitution of “Friendship” - Dreher, Jochen (SocietàMutamentoPolitica, 2016)
This analysis combines phenomenological and sociological research for an investigation of the social relationship of “friendship”. From a phenomenological perspective, it focuses on the epistemological basis, on the subjective constitution of the phenomenon of “friendship”. The social construction of friendship however, is described from a sociological research perspective with reference to concrete empirical expressions of this specific social relationship. The key for the reflections on friendship is the adaptation of Edmund Husserl’s method of phenomenological reduction for the analysis of social phenomena, based on the argumentations of Alfred Schutz and Aron Gurwitsch. This leads to the assumption that friendship is symbolically constituted with reference to everyday transcendent ideas which substantially define the specific expression of this social relationship.